Analysis of total phenolics and flavonoids content from methanol extract of Caesalpinia bonduc (L.) Roxb. seeds and antioxidant activity assay - Samriani Samriani; Hasnah Natsir; Seniwati Dali; Abdul Wahid Wahab; Nunuk Hariani Soekamto; Paulina Taba (RAFFLESIA JOURNAL OF NATURAL AND APPLIED SCIENCES, 2022)
Caesalpinia bonduc (L.) Roxb. seed is known as gorek seed contain secondary metabolites such as alkaloids, tannins, flavonoids, and phenolics, due to the content of these secondary metabolites so that this plant has antioxidant activity. This study aimed to determine total phenolic and flavonoid contents of methanol extract of gorek C. bonduc seeds as well as antioxidant activity. Extraction of gorek C. bonduc seeds was carried out with methanol, then quantitative determination of total phenolic by the Folin-Ciocalteu method as Gallic Acid Equivalent (GAE)/gram of extract, flavonoid content by AlCl3 method as Quercetin Equivalent (QE)/gram of extract, and in vitro antioxidant activity with DPPH (2,2-diphenyl-1-picrylhydrazyl) method was in IC50 (inhibition concentration). Based on the results of research, the phytochemical screening of methanol extract of gorek C. bonduc seeds showed alkaloids, flavonoids, saponins, tannins, and phenolics. The determination of the total phenolic and flavonoid content were obtained 0.55 ± 0.02 mgGAE/g and 0.50 ± 0.02 mgQE/g, respectively. The antioxidant activity of methanol extracts and ascorbic acid showed IC50 values were 3770.77 ppm and 3.36 ppm respectively.